Hubungan Pemanfaatan Lingkungan Sekolah sebagai Sumber Belajar dengan Hasil Belajar Kognitif IPA Peserta Didik - Salmawati, Salmawati; Rahman, Adi Putra; Hajar, Ibnu (Al-AHYA: Jurnal Pendidikan Biologi, 2024)
This research aims to determine the relationship between the use of the school environment as a learning resource and students' cognitive science learning outcomes. This research used an exploratory approach with a quantitative methodology of ex post facto, with a simple association design. The population was all class VII students at SMPN 4 Polewali, totaling 215 people for the academic year 2022–2023. Sampling used a probability sampling technique with Simple Random Sampling method of the Slovin formula. The research instrument consisted of a questionnaire and documentation. Data analysis techniques used descriptive statistical methods and inferential statistics. In the analysis of the research data, the Sig value of the decision-making data was obtained (0.00) < 0.05, with the level of relationship being in the low category with a value of 0.320. The correlation coefficient value (r = 0.320) interpreted that the contribution of the school environment utilization variable is only 10.24%, while the remaining 89.76% is contributed by other variables outside of school environment utilization.